Slavonia Hotel System - Nebojša Antešević; Jasenka Kranjčević (Prostor, 2025)
A project that stands out among Croatian hotel architecture of the second half of the 20th century is the unique Slavonia Hotel System (SHS), designed in the mid-1970s by a team of experts from the Urban Institute of Croatia and headed by architect Matija Salaj. The SHS project was based on the principle of standardization in terms of spatial-functional organization, architectural design, interior design, furnishing and visual communication elements as well as operation and market penetration, and was envisaged as the driving force behind continental tourism development in Slavonia and Baranja. This paper examines the planning framework, program specifications, and urban-architectural design of the hospitality and tourist facilities of the SHS (including a city hotel model in two variations, a spa hotel, and a motel) by utilizing sources from Salaj’s estate and archival documentation from the Urban Institute. Notably, it includes Salaj’s explanations of the SHS project and his perspectives on the features of hospitality and tourist facility architecture, as presented in professional journals and conference publications. These aspects are complemented by a review of tourism development trends in the 1970s and the characteristics of hotel architecture in market economy.